Hemoglobin as a possible biochemical index of hypertension-induced vascular damage. Issue 1 (December 2015) - Shimizu, Yuji; Kadota, Koichiro; Nakazato, Mio; Noguchi, Yuko; Koyamatsu, Jun; Yamanashi, Hirotomo; Nagayoshi, Mako; Nagata, Shuichi; Arima, Kazuhiko; Maeda, Takahiro
Abstract Background We previously reported on the positive association of hemoglobin with hypertension and atherosclerosis. On the other hand, hepatocyte growth factor (HGF) has been evaluated as a possible biochemical index of hypertension-induced vascular damage. However, no studies have reported on a correlation between hemoglobin and HGF accounting for hypertension status. Methods A cross-sectional study of 1108 subjects (392 men and 716 women, 40–93 years old) who were undergoing a general checkup in 2014 was conducted. Results Multiple linear regression analysis adjustment for known cardiovascular risk factors showed no significant correlation between hemoglobin and HGF in non-hypertensive subjects, but a significant positive correlation in hypertensive subjects;β (parameter estimate) = 0.3 (p = 0.975) for non-hypertensive men, β = 0.4 (p = 0.925) for non-hypertensive women, β = 32.7 (p < 0.001) for hypertensive men, andβ = 18.7 (p = 0.002) for hypertensive women. Conclusion We found a significant positive correlation between hemoglobin and HGF among hypertensive men and women. Like HGF, hemoglobin may be a useful indicator to evaluate hypertension-induced vascular damage. Since hemoglobin can easily be measured, these results support hemoglobin as an efficient tool to evaluate vascular damage induced by hypertension in daily medical practice.